Streptococcal toxic shock syndrome in the setting of recent gynecologic surgery: A case report - Michelle Gruttadauria; Jennifer Pollard; Sara Kim; Xun Lian (Elsevier, 2021)
Toxic shock syndrome (TSS) is an acute, toxin-mediated disease process which is commonly caused by Staphylococcus aureus or Streptococcus pyogenes. A high level of clinical suspicion is imperative, with prompt antibiotic therapy with a penicillinase-resistant penicillin (vancomycin in areas with increased methicillin-resistant Staphylococcus aureus) and clindamycin, given the high morbidity and mortality. Here, a case is reported of streptococcal-mediated TSS in a 37-year-old woman with a history of endometriosis, four days after a laparoscopic cystectomy; an intrauterine device (IUD) was left in situ at the time of uterine manipulation and not removed until hospital day 3 of the patient's readmission. Although no specific guidelines exist for removing IUDs, it is a foreign body and therefore it is recommended that early removal be considered regardless of the level of suspicion that it is the source of sepsis.